The Effect Of Performance Expectancy, Effort Expectancy, Social Influence, Perceived Risk, And Perceived Cost On Behavioral Intention In The Use Of Dana E-Wallet In Bandung City - Maitimu, Reny Joseli; Hidayahtullah, Deden Syarif (UNIVERSITAS PAKUAN, 2024)
Technological advances in this digital era greatly affect the way consumers behave and with the times in the digital era according to Bank Indonesia regulations, technological developments and information systems continue to produce various innovations, especially financial technology in order to meet the needs of the community, including in the field of payment system services, both in terms of instruments, organizers, mechanisms, and infrastructure for organizing payment transaction processes, currently PT Espay Debit Indonesia Koe or better known as DANA Digital Wallet which is a digital payment platform used by various applications, online and conventional outlets everywhere. The purpose of this study was to determine the effect of performance experience, effort expectancy, social influence, perceived risk, perceived cost on behavioral intention in DANA digital wallet users in Bandung City. Quantitative method with descriptive research type is used in this research, with non-probability sampling purposive sampling method of 400 samples who are DANA e-wallet users in Bandung City. Partial Least Square Structural Equation Modeling (PLS-SEM) was used for data analysis in this study. The results concluded that the Performance Expectancy variable has a positive and significant effect on behavioral intention. Effort Expectancy has a positive and significant effect on behavioral intention. Social influence has a positive and significant effect on behavioral intention. Perceived Risk also has a positive and significant effect on behavioral intention. Perceived Cost has a positive and significant effect on behavioral intention.